Itô's formula with respect to fractional Brownian motion and its application. (1996) - Dai, W.; Heyde, C. C.
Abstract : Fractional Brownian motion (FBM) with Hurst index 1 / 2 < H < 1 is not a semimartingale. Consequently, the standard Itô calculus is not available for stochastic integrals with respect to FBM as an integrator if 1 / 2 < H < 1 . In this paper we derive a version of Itô's formula for fractional Brownian motion. Then, as an application, we propose and study a fractional Brownian Scholes stochastic model which includes the standard Black-Scholes model as a special case and is able to account for long range dependence in modeling the price of a risky asset. This article is dedicated to the memory of Roland L. Dobrushin.